Pembuatan Keset Srabut Kelapa untuk peningkatan Ekonomi Masyarakat Sidomulyo, Gunungkidul - Purnomo, Sigit; Hidayatullah, Ahmad Syuqi; Taufik, Yudan; Wijayanti, Dela Tri; Nugroho, Irfan Adi (Piramida Akademi, 2023)
Purpose − Making coconut fiber doormats with the aim of producing coconut fiber doormats to help reduce coconut waste produced from the coconut processing industry. This supports more sustainable and environmentally friendly processing practices in Sidomulyo Hamlet, Sampang, Gedangsari, Gunungkidul. Coconut fiber is a natural, renewable material. Using coconut fiber to make doormats supports environmental sustainability because it reduces dependence on synthetic materials or plastic.. Method − Activities in the form of training in making coconut fiber mats. The activity process informs the public about how to make coconut fiber mats. Mat products made from coconut fiber help reduce coconut waste produced from the coconut processing industry. This supports more sustainable and environmentally friendly processing practices . Findings − This activity was participated in by the Sidomulyo Hamlet Community, RT 01, 02, 03 and 04, at the Sidomulyo Hamlet Hall, RT 02. This activity was enthusiastically welcomed by the mothers of Sidomulyo residents who were interested in coconut fiber mats being used to clean floors and other surfaces at home. , office, or public place. The coarse fibers of coconut fiber help lift dust, dirt, and other small particles from surfaces.